A.P, ADAGBO CHARACTERIZATION OF AQUACULTURE EARTHEN POND SOILS IN UMUDIKE AND MAKURDI METROPOLIS - ADAGBO, A.P.; ATAGUBA, G.A.; OMEJI, S. (Nigerian Journal of Fisheries, 2026)
Bottom soils were collected from selected earthen ponds with 5cm diameter core tubes at a depth of 10cm of the pond bottom. The study investigated the physical, chemical, soil profile, mechanical, aquaculture pond soil texture, and water quality characteristics of selected fish ponds in Umudike and Makurdi Metropolis. In the results obtained, Umudike had higher sand content than Makurdi, regardless of season. In the dry season, Umudike had 72.00% compared to 54.50% in Makurdi, and in the Wet Season, Umudike had 69.90% compared to 63.80% in Makurdi. Makurdi had higher clay content (28.20% in the dry season and 25.60% in the wet season) than Umudike (18.20% in the dry season and 18.30% in the wet season). Makurdi had a substantially higher particle density than Umudike. Both locations had similar moisture levels (Makurdi:18%, Umudike:17.7%) during the dry season. Organic matter values were also consistent across seasons and locations, ranging from 1.50% to 1.54%. The results obtained from water quality parameters showed that there were significant effects in dissolved oxygen for both seasons and locations (p<0.001) but no significant interaction (p=0.318). Values of biological oxygen demand were similar across both locations and seasons, ranging from 0.07 to 0.15mg/L. Both locations had similar temperatures ( 29.6 - 29.7C) during the dry season, while temperatures were lower, ranging from 27.7C to 28. 6ºC.during the wet season.Turbidity values varied across seasons, with Makurdi showing higher turbidity in the dry season (12.80 NTU) compared to the wet season (6.37 NTU).The results obtained from this work proved that there was a significant difference, p<0.01, in the soil and water quality parameters of the two locations and seasons. The soil types in the two locations are similar and suitable for aquaculture.